Challenges and innovations in Primary Health Care in the Amazon: A Scoping Review. (30th September 2020) - Sousa, A; Wallace, C; Farmer, J; Herkrath, F J; Bousquat, A
Abstract: Background: The Amazon region crosses the territorial borders of nine countries with a vast complexity of ecological and social relations. Outside of large and medium cities, this region comprises a mosaic of ranches, villages, farms, isolated houses and small towns scattered over a vast territory, in large part accessed only by waterway. Working with health in this region requires specific strategies that respect the dynamics of this place. This research aimed to reveal the challenges and innovations of Primary Health Care (PHC) in places outside the largest cities in the Amazon. Methods: The scoping review methodology was applied to peer-reviewed articles. Six databases were searched to identify scientific papers published in English, Spanish and Portuguese between January 2000 and November 2019. The analytical strategy was to combine descriptive statistics and qualitative content analysis to extract from each article all the content related to the research questions. Results: This review included 26 papers. The most frequent challenges reported in the studies were related to the way of working (8), specific training for professionals (5), leadership and governance (4) and infrastructure improvement (2). A smaller number of studies were dedicated to innovative experiences, which approached training and methodologies for health agents recruited in the communities (4), technologies to the services (2) and a river unit as a model to work in Amazon(1). Conclusions: The challenges presented in this review indicate the need to build services that are more sensitive to Amazonian locations and the need to train professionals for this region. Also, it revealed innovations with positive impacts which can be taken as key lessons regarding the functioning of PHC in the Amazon. Key messages: This research fills a knowledge gap about PHC in the Amazon. The challenges and innovations presented in the review provide insights to assist PHC policy makers and managers with the design and delivery of health services in the Amazon.